Experiences, challenges and strategies of grandmothers solely responsible for the care of very young children of overseas Filipino worker parents - Romero, Florante D.; Agustin, Estrella R. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
Abstract
Thesis (M.F.L.C.D.)--University of the Philippines Diliman
Keywords: Child care -- Philippines; Grandmothers -- Philippines; Foreign workers, Filipino; Godparent and child -- Philippines; Families -- Philippines